The Plays of Shakespeare’s Late Period and "The Man in a Panther-Skin" - Khintibidze, Elguja (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
The last plays by Shakespeare reveal reminiscences from the love story of Nestan and Tariel from the MPS being the direct literary source of Shakespeare’s 3 plays by his contemporaries: "Cymbeline", "Philaster", "A king and No King".